The relationship between task – technology fit and job perfomance among employees in Sekolah Kebangsaan (P) Methodist 2 Melaka / Nur Athira Nasharuddin - Nasharuddin, Nur Athira (Faculty of Business and Management, 2013)
Information systems is one of the important item that must be used in all organization because this information systems can helps to access more information accurately and relevant. This study is to increase the understanding in identifying the answers for all consequences of the study which to identify the relationship between task technology fit and job performance enlployees in Sekolah Kebangsaan (P) Methodist 2 Melaka.Besides that, the researcher also focused on the task-technology fit which is the degree to a technology that assists an individual in performing his or her portfolio of tasks and specifically task-technology fit is the correspondence between task requirements, individual abilities and the functionality of the technology (Goodhue & Thompson, 1995)~ The study involved 44 respondents which is staff and teachers which include the Headmistresso The results shown were depending on eight measurements that used in describing the characteristics of task-technology fit and Sekolah -Kebangsaan (P) Methodist 2, Melaka employee clarification of their job performance. In addition, this study also helps the employee to perform their job smoothly and successfully and to achieve the organization goal.